Design and Optimization of Energy-Efficient Power Electronics for Next-Generation Electric Vehicles - H. Ashour; David Gichoya (National Journal of Electrical Electronics and Automation Technologies, 2025)
The explosive development of electric vehicles (EVs) requires the use of very efficient, small and dependable power electronics to maximize energy conversion, distribution, and storage. The work presented seeks to propose and test a full design and optimization procedure of energy-efficient power electronics in a future generation of EVs, aiming at a better performance, high driving range, and high-temperature stability. The approach combines the use of the wide-bandgap semiconductor (silicon carbide and gallium nitride) devices (SiC MOSFETs and GaN HEMTs) with multi-objective optimization algorithms that reduce the conduction and switching losses. The control temperatures to be thermal-aware and also the addition of better thermal cooling schemes are also provided to be more stable at times of high load. To succinctly outline the proposed architecture which consists of a SiC based traction inverter, a GaN based bidirectional DC-DC converter and a high-efficiency onboard charger, our multi-stage architecture is modeled in MATLAB/Simulink and validated on an OPAL-RT hardware-in-the-loop (HIL) platform. In comparison with traditional silicon-based system, benchmarking shows a potential performance-gain to be as high as 7.8%, the thermal rise is up to 27.8% lower, and power density to rise by a substantial 45 percent. Achieved results reveal that WBG-based power electronics can address the high efficiency and reliability demands of EV platforms in the future. The method suggested has a viable route of leading to eco-friendly, high-performance electric mobility systems.